Antitumor Activities and Cellular Changes Induced by TrkB Inhibition in Medulloblastoma - Thomaz, Amanda; Pinheiro, Kelly de Vargas; Souza, Bárbara Kunzler; Gregianin, Lauro; Brunetto, Algemir L.; Brunetto, André T.; de Farias, Caroline Brunetto; Jaeger, Mariane da Cunha; Ramaswamy, Vijay; Nör, Carolina; Taylor, Michael D.; Roesler, Rafael (Frontiers in Pharmacology, 2019)
Neurotrophins are critically involved in regulating normal neural development and plasticity. Brain-derived neurotrophic factor (BDNF), a neurotrophin that acts by binding to the tropomyosin receptor kinase B (TrkB) receptor, has also been implicated in the progression of several types of cancer. However, its role in medulloblastoma (MB), the most common type of malignant brain tumor afflicting children, remains unclear. Here we show that selective TrkB inhibition with the small molecule compound ANA-12 impaired proliferation and viability of human UW228 and D283 MB cells, and slowed the growth of MB tumors xenografted into nude mice. These effects were accompanied by increased apoptosis, reduced extracellular-regulated kinase (ERK) activity, increased expression of signal transducer and activator of transcription 3 (STAT3), and differential modulation of p21 expression dependent on the cell line. In addition, MB cells treated with ANA-12 showed morphological alterations consistent with differentiation, increased levels of the neural differentiation marker β-III Tubulin (TUBB3), and reduced expression of the stemness marker Nestin. These findings are consistent with the possibility that selective TrkB inhibition can display consistent anticancer effects in MB, possibly by modulating intracellular signaling and gene expression related to tumor progression, apoptosis, and differentiation.